Advances in immune checkpoint inhibitors induced-cardiotoxicity - Li, Xiang; Peng, Wenying; Wu, Jiao; Yeung, Sai-Ching Jim; Yang, Runxiang (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs) are approved as the first-line drug for treating many cancers and has shown significant survival benefits; however, it also causes immune-related adverse events (irAEs) while activating the immune system, involving multiple organs. Among them, cardiovascular immune-related adverse events (CV-irAE) are rare, but common causes of death in ICIs treated cancer patients, which manifest as myocardial, pericardial, vascular and other cardiovascular toxicities. Therefore, it is important that irAEs, especially CV-irAE should be carefully recognized and monitored during the whole ICIs treatment because early detection and treatment of CV-irAE can significantly reduce the mortality of such patients. Consequently, it is urgent to fully understand the mechanism and management strategies of CV-irAE. The effects of ICIs are multifaceted and the exact mechanism of CV-irAE is still elusive. Generally, T cells identify tumor cell antigens as well as antigen in cardiomyocytes that are the same as or homologous to those on tumor cells, thus causing myocardial damage. In addition, ICIs promote formation of cardiac troponin I (cTnI) that induces cardiac dysfunction and myocardial dilatation; moreover, ICIs also increase the production of cytokines, which promote infiltration of inflammation-linked molecules into off-target tissues. Currently, the management and treatment of cardiovascular toxicity are largely dependent on glucocorticoids, more strategies for prevention and treatment of CV-irAE, such as predictive markers are being explored. This review discusses risk factors, potential pathophysiological mechanisms, clinical manifestations, and management and treatment of CV-irAE, guiding the development of more effective prevention, treatment and management strategies in the future.